Improving the Law on International Treaties 2016 from the Perspective of Legal Document Drafting Techniques - Dao, Le Thi Anh (VNU Journal of Science: Legal Studies; Vol 39 No 4, 2023)
The quality of a legal document is affected by its drafting techniques. The Law on International Treaties 2016 was promulgated before the issuance of Resolution No. 351/2017/UBTVQH14 dated March 14, 2017, which stipulates the format and drafting techniques of legal documents. This article analyzes the technical limitations of the Law on International Treaties 2016, including issues related to its structure, the lack of text cohesion, and the inconsistencies in expression and word usage. In addition, the author makes several recommendations to improve drafting techniques of this Law.